PENYELESAIAN SENGKETA WANPRESTASI ANTARA PT. PLN (PERSERO) APP BALI DENGAN PT.GLOBAL TWIN STAR MELALUI JALUR NEGOSIASI - Eka Rahmat Andrianto; I Made Wirya Darma (Jurnal Analisis Hukum, 2018)
State-owned Enterprise PT.PLN (persero) App Bali made a tender on travo 150/20 jobs. The tender was won by PT. Global Twin Star, in it’s work there are disputes in the contract agreement. So from this dispute the author takes the formulation of the problem as follows. How to resolve disputes between the two sides. The second is how the implementation of the settlement results through negotiations. The purpose of the writer is to know and analyze how the results of the settlement through negotiations and also find out whether this implementation is very relevant for both parties each achieved. Agreement made and agreed by PT. PLN (Persero) with PT. Twin Star applies as a law for both parties or called the principle pacta sunt servanda. Settlement through Alternative Dispute Resolution is based on the spirit of win-win solution. Therefore, taking into account future interests, then from the parties to the dispute there must be a desire to maintain their good relationship. Implementation obtained is a continuous relationship of work between the two sides. Where the PT. Global twin star gets additional work from PLN to maintain existing transformer and owned PT.PLN. PLN's transformer is well maintained until the work is done. In a business dispute the parties prefer to avoid to resolve their dispute through the courts. setlement of specific defaults disputes and business disputes in general to be resolved through atlernative negotiated settlement disputes. This is because the company's good name is maintained, cost and time are also more efficient if through this path. The result of dispute resolution through alternative dispute resolution, able to merely render the objectives of the law itself, namely justice, certainty and benefit.Keywords: Dispute Settlement, Wanprestasi, Negotiation.